Expression characteristics of piRNAs in ovine luteal phase and follicular phase ovaries - Li, Chunyan; Zhang, Rensen; Zhang, Zijun; Ren, Chunhuan; Wang, Xiangyu; He, Xiaoyun; Mwacharo, Joram Mwashigadi; Zhang, Xiaosheng; Zhang, Jinlong; Di, Ran; Chu, Mingxing (Frontiers in Veterinary Science, 2022)
PIWI-interacting RNAs (piRNAs), a novel class of small non-coding RNAs that have been shown to be indispensable in germline integrity and stem cell development. However, the expressed characteristics and regulatory roles of piRNAs during different reproductive phases of animals remain unknown. In this study, we investigated the piRNAs expression profiles in ovaries of sheep during luteal phase (LP) and follicular phase (FP) using Solexa sequencing technique. A total of 85,219 and 127,156 piRNAs tags were identified in ovine ovaries across the two phases. Most expressed piRNAs start with uracil. piRNAs with a length of 24 nt or 27-29 nts accounted for the largest proportion. Obvious ping-pong signature appeared in FP ovary. The piRNA clusters in sheep ovary were unevenly distributed on the chromosomes, with high density on Chr 3 and 1. For genome distribution, piRNAs in sheep ovary were mainly derived from intron, CDS and repeat sequence regions. Compared to LP ovary, a greater number of expressed piRNA clusters were detected in FP ovary. Simultaneously, we identified 271 differentially expressed (DE) piRNAs between LP and FP ovaries, with 96 of piRNAs upregulated and 175 of piRNAs downregulated, respectively. Functional enrichment analysis (GO and KEGG) indicated that their target genes were enriched in reproduction-related pathways including oocyte meiosis, PI3K-Akt, Wnt and TGF-β signaling pathways. Together, our results highlighted the sequence and expression characteristics of the piRNAs in sheep ovary, will help understand the roles of piRNAs in ovine estrus cycle.